Human Security Implications of Foreign Military Bases in Djibouti - Onor, Kester C (Universitas Medan Area, 2023)
The principles of sovereignty and non-interference have historically shaped China's foreign policy, serving as fundamental tenets to safeguard the nation from external interventions, particularly during and after the Cold War. However, in recent times, there has been a noticeable shift in China's foreign policy as it embarks on an unprecedented expansion of its military presence beyond its borders. This shift is exemplified by the establishment of a permanent military base in Djibouti, situated in the Middle East and North African (MENA) region, which China refers to as